Model Based Assessment of Performance of Lithium-Ion Batteries Using Single Ion Conducting Electrolytes. (10th September 2018) - Wolff, Nicolas; Röder, Fridolin; Krewer, Ulrike
Abstract: Single ion conductors, such as solid electrolytes are promising alternatives to overcome drawbacks of lithium-ion batteries with binary electrolytes, e.g. thermal runaway and electrolyte decomposition. Within this research a pseudo-two-dimensional (P2D) battery model for cells with single ion conducting electrolytes is derived and compared to a state of the art P2D model for cells with binary electrolytes to elucidate the theoretical differences in cell performance when replacing binary with single ion conducting electrolytes, as well as the related advantages and bottlenecks. At high discharge rates, electrolyte potential losses are more distinct for binary electrolytes compared to single ion conducting electrolytes which results in a higher energy for the latter one. Further, sensitivity to variations in electrode and electrolyte are elucidated analyzing discharge curves, Electrochemical Impedance Spectroscopy (EIS) and maximal energy. Parameter variations indicate that single ion conducting electrolyte cells allow thick electrode designs. They can therefore be advantageous to classical binary electrolyte cells when building high energy cells, once the high conductivities of laboratory studies found their way into application.